BIOACTIVE COMPOUNDS OF STREPTOMYCES QUS7 ISOLATE ETHYL ACETATE EXTRACT FROM SEDIMENT IN ALDIWANYIA RIVER (World Bulletin of Public Health, 2022)
This study was subjected for the first time to Streptomyces sp. QUS7 has been identified and described using morphological and biochemical characteristics from the sediment of the Al-Diwaniya River in southern Iraq. Extract of the ethyl acetate was tested with GC-MS. The strain was identified as the genus Streptomyces based on biochemical, microbiological, and morphological characteristics. 2,4-bis(1,1-dimethylethyl)-phenol, pentadecanoic acid, tetradecene, methyl ester, 14-methyl-, 1-Hcycloprop(e)azulen-7-ol, decahydro-1,1,7-trimethyl-, 4-methylene, hexadecene-2-pentadecanone, 6,10,14-trimethyl, hexadec Nonacosan Additional. the study is needed to clarify the antimicrobial agent's structure and purification